Gêneros orais na produção textual do ensino médio - Osias, Juliene Paiva de Araújo (2006)
The oral genders are, necessarily, present in the daily routine of anyone who speaks any language, spontaneously. Therefore, in the case of primary genders, they are not taught. The fact is that the formal oral genders not only could but they also would have been side by side the writing, comprising school programs, instead of considering writing as the correct and acceptable form to comunicate tendency which insists on relegating the oral language to a platform of inferiority and inaccuracy. Didactic Books do the same, and, in Secondary Education, there is a simple continuity of this mentality. According to this discussion, we propose analysing, from a Portuguese Didactic Book , if this Didactic Book treats the oral genders as a teaching object and it does that. Then we will observe that the oral teaching is still in its beginning, specially in Secondary Education, when the writing acts as a protagonist.